Kegiatan Pengabdian Masyarakat Melalui Kampanye Lindungi Bumi: Berhenti Membuang Sampah Sembarangan Dan Mulailah Mendaur Ulang - Adi Wibawa; Muhammad Ridha Iswardhana; Maria Stephanie Olivia Jawa; Faisal Hasibuan; Annisa Rahmatin; Jescinka Priendisaputri; Dian Inda Yani (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2024)
The waste problem is a reality that often occurs in big cities, such as Yogyakarta. Even though the Special Region of Yogyakarta is a world tourism destination. One tourist attraction that has a waste challenge is Alun-Alun Kidul Yogyakarta. This is because many people do not yet have an understanding of proper waste management. Many visitors to Alun-Alun Kidul Yogyakarta throw rubbish carelessly. Meanwhile, the available trash bins are limited and uneven. This service aims to provide an invitation to the wider community about the dangers and management of waste. Campaign activities were carried out on Friday, April 19 2024 at Alun-alun Kidul Yogyakarta. Based on the implementation of this service, not all visitors and sellers in the area understand about disposing of waste properly. However, the majority of the audience already knows, it just requires more humanistic education. This reality shows that tourists and residents can be agents of change in protecting the environment from waste.